Stranding of a Risso's dolphin (Cetacea, Delphinidae) on the north-eastern coast of Brazil, with comments on its distribution and threats in the Western South Atlantic. (20th May 2015) - Toledo, Gustavo Alves da Costa; Gurgel Filho, Newton Mota; Brito, Jadson Luis da Silva; Langguth, Alfredo
Abstract : The Risso's dolphins, Grampus griseus, are widely distributed, moderately large delphinids, inhabiting deep waters of the continental slope and outer shelf through the tropics and temperate regions. Until recently, their occurrence in the Western South Atlantic (WSA) ocean was poorly documented. This paper reports the first stranding record in the state of Paraíba (6°57′45″S 34°51′28″W), on the north-eastern coast of Brazil. Information on measurements, cause of death and the mapping of 46 records of G. griseus are provided. The data summarized in this report suggests that the distribution of G. griseus is continuous in the WSA, but with a higher frequency in colder waters further south. The available information for the WSA showed that negative interactions between Risso's dolphins and fisheries are more frequent in Brazil and need further investigation for conservation purposes.